Analisis Faktor-Faktor Penyebab Terjadinya Perubahan Desain dan Pengaruhnya terhadap Cost overrun Proyek Konstruksi di Jambi - Azanna, Dwitya Okky; Handayani, Elvira; Andreawan, Muhammad Fiqh (Jurnal Talenta Sipil, 2024)
This research aims to prove empirically the factors that cause design changes and the impact of cost overruns on construction projects. The data collection technique used was primary data collection with a sample of 10 respondents taken from contractor project staff of construction projects in Jambi City. The sampling technique in this research used probability sampling and stratified random sampling methods. Data analysis processing in this study used IBM SPSS 28. The final results of this analysis found that the causative factor of design changes because of owner or contractor. The most dominant design change factors caused by the owner were delays in providing goods that should have been provided by the owner at 48.48%, temporary suspension at 42.85%, and termination of construction contracts at 56.81%. Apart from that, other dominant factors in design changes caused by contractors are delays in providing design drawings for construction that have been approved, amounting to 62.5%, design/specification defects equal in value to the number of addendums issued at the implementation stage, namely 60.60%, final failure of contractor/subcontractor performance was 64.51%.